The Influence Of Financial Stability, Change In Director, Political Connection, Nature Of Industry, Change In Auditor, And Ceo Duality On Fraud Detection - Ayunda, Ni Luh Kirana Maheswari Putri; Amirya, Mirna (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to examine the effects of fraud factors described in the fraud hexagon theory. According to this theory, there are six elements influencing fraudulent behavior: pressure, opportunity, rationalization, capability, arrogance, and collusion. Beneish M-Score was used in this study to detect fraud. From the population of insurance companies listed in the Financial Services Authority during the 2019–2023 period, 46 companies were selected as samples using purposive sampling. Using logistic regression analysis, this study finds that pressure and opportunity, which are proxied by financial stability and the nature of the industry, have positive effects on fraud detection. Meanwhile, capability proxied by change in director, collusion proxied by political connection, rationalization proxied by change in auditor, and arrogance proxied by CEO duality have no effect on fraud detection.